Transforming BPMN Notation into Java Code - Hriberšek, Janko; Leskovar, Robert; Baggia, Alenka (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Introducing blockchain technology brings new opportunities to automate and improve operational efficiency, particularly using smart contracts that automate the implementation of business rules. BPMN, an established standard for business process modelling, can be used to develop smart contracts. This paper presents the transformation of BPMN models into Java code framework that can be used in a blockchain technology environment, specifically on the HyperLedger Fabric platform. The graphical representation of BPMN processes is written in XML format, from which the basic BPMN building blocks can be implemented as control structures in Java program code. The proposed solution enables fast, accurate and scalable conversion of BPMN models, thereby optimising the development of smart contracts. The paper opens opportunities for further research and extension of the methodology by incorporating more complex BPMN building blocks and adaptations for different blockchain technology environments.